2020
DOI: 10.17126/joralres.2020.081
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum level of 25-hydroxy vitamin D with Oral Lichen Planus. A case-control study.

Abstract: Introduction: Vitamin D deficiency is a global health problem that can be a risk factor for a broad range of diseases such as some autoimmune diseases. Due to the autoimmune base of lichen planus, it seems that a reduction of the serum level of vitamin D is related to lichen planus. In this study, we investigate the relation between serum level of vitamin D and oral lichen planus patients (OLP). Material and Methods: In this case-control study, 35 patients with OLP (including 15 men and 20 women) and 70 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…The T-test results showed a statistically significantly lower serum vitamin D concentration in the OLP group compared to the control group (p=0.001). These results confirm the study of Sadeghi et al, who found a statistically significantly lower vitamin D serum concentration in OLP patients ( 9 ). On the other side, the research by Bahramian et al ( 10 ) and the systematic review and meta-analysis by Sakthivel et al ( 11 ) found no statistically significant difference in serum vitamin D concentration between the OLP patients and the control group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The T-test results showed a statistically significantly lower serum vitamin D concentration in the OLP group compared to the control group (p=0.001). These results confirm the study of Sadeghi et al, who found a statistically significantly lower vitamin D serum concentration in OLP patients ( 9 ). On the other side, the research by Bahramian et al ( 10 ) and the systematic review and meta-analysis by Sakthivel et al ( 11 ) found no statistically significant difference in serum vitamin D concentration between the OLP patients and the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Vitamin D may play a role in the development or severity of the clinical picture of symptomatic forms of OLP by regulating immune system function ( 9 ). Active forms of vitamin D have a regulatory role in the expression of several genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existe amplia evidencia que bajos niveles séricos de VD se relacionan con una respuesta inflamatoria exagerada, presente en diversas patologías de carácter autoinmune, por lo que, recientemente investigaciones han buscado cuantificar la concentración sérica de VD en pacientes con LPO (Bahramian et al, 2018;Sadeghi et al, 2020). Los autores concluyeron que los niveles plasmáticos de VD en pacientes que padecían LPO son significativamente menores que los pacientes del grupo control (Bahramian et al, 2018;Sadeghi et al, 2020;Motahari et al, 2020;Sridharan & Sivaramakrishnan, 2021). También relatan la asociación entre liquen plano y el desarrollo de lesiones orales potencialmente malignas en algunos casos, por lo que la VD y su rol inmunomodulador e inflamatorio deben ser analizadas para prevenir esta enfermedad.…”
Section: Discussionunclassified